2020
DOI: 10.22159/ijpps.2020v12i5.37374
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Enhancement of Coriandrum Sativum Using Plant Biologicals

Abstract: Objective: The present study was designed to investigate phytopromotional effects of Sebacina vermifera on economically and medicinally important aromatic plant - Coriandrum sativum (coriander). Methods: Phytopromotional effects of Sebacina vermifera were evaluated on coriander, under greenhouse and field conditions. The evaluations were carried out with reference to emergence, growth promotion and quantitative as well as the qualitative composition of essential oil. Beside this the overall effects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Population size was 100 for each replicate of an observational group. All experimentation was done in six replicates, and the sample size was also six from each replicates 22 . A complete topography of field experimentation and sowing scheme is given in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Population size was 100 for each replicate of an observational group. All experimentation was done in six replicates, and the sample size was also six from each replicates 22 . A complete topography of field experimentation and sowing scheme is given in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Also, P. fluorescens has investigated to increase the EO in Ocimum basilicum and Origanum majorana 67,68 . Prior investigations demonstrated that S. vermifera significantly increased the yield of EO in Coriandrum Sativum 22 , Foeniculum vulgare 35 , T. vulgaris 37 .…”
Section: Fig 6: Effect Of Treatments On (A) Total Length Of Plants (B) Total Fresh Weight Of Plants (C) Total Dry Weight Of Plants Under mentioning
confidence: 97%
See 2 more Smart Citations
“…S. vermifera enhanced the major chemical components including monoterpene alcohol (linalool) and monoterpene hydrocarbon (α-pinene and β-pinene) of coriander seeds. 12 In general, pure culture of arbuscular mycorrhizal fungi (AMF) not cultivable outside the host, but S. vermifera is a potential AM-like fungi which is cultivable under lab conditions. 13 AMF colonized plants may show increased biomass, faster growth rate & maturity, resistance to biotic and abiotic stresses, and more effective photosynthesis, enhanced yield and better composition of EO.…”
Section: Introductionmentioning
confidence: 99%